PENGARUH ROMBONGAN BELAJAR SISWA TERHADAP PERKEMBANGAN KOGNITIF SOSIAL PESERTA DIDIK DI MI MA'ARIF NGAMPELDENTO SALAMAN KABUPATEN MAGELANG JAWA TENGAH - Siti Anisatun Nafi'ah; Muhammad Islakhudin (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2020)
Abstrak The Influence of Student Study Groups on the Social Cognitive Development of Students in the Mi Ma'arif Ngampeldento Salaman Kab. Magelang, Central Java. The number of students in a class can influence learning in the classroom. Students who are too many or too few will have an impact on the developmental psychology of students especially the child's social cognitive. Because the ideal number of students will occur social interaction between students so that learning can run effectively.Data collection techniques in this study used interview and observation techniques. Data analysis techniques used in this study with descriptive research, a researcher conducts the analysis only up to the description level, namely analyzing and presenting facts systematically so that it can be more easily understood and concluded. Based on the results of the study that the number of students a little does not always show the social cognitive of students is good, but on the contrary the social cognitive of students in MI Ma'arif Ngampeldento is low. There are several factors, namely (1) Lack of exchange of ideas between students due to the small number of friends in the school environment. (2) The lack of interaction between students in the school environment. (3) there are no peers in one school that lives the same / close. (4) the geographical location of the children's school environment which is far from the city center. (5) Lack of parental care in children's cognitive development. (6) Teachers who are less capable in carrying out their duties.   Abstrak Pengaruh Rombongan Belajar Siswa Terhadap Perkembangan Kognitif Sosial Peserta Didik Di Mi Ma'arif Ngampeldento Salaman Kab.Magelang Jawa Tengah. Jumlah siswa dalam suatu kelas dapat mempengaruhi pembelajaran di dalam kelas. Siswa yang terlalu banyak atau terlalu sedikit akan berdampak pada psikologi perkembangan peserta didik khusunya kognitif sosial anak. Karena jumlah siswa yang ideal akan terjadi interaksi sosial antar peserta didik sehingga pembelajaran dapat berjalan efektif. Teknik pengumpulan data dalam penelitian ini menggunakan teknik wawancara dan observasi. Teknik analisis data yang digunakan dalam penelitian ini dengan penelitian deskripsi, seorang peneliti melakukan analisis hanya sampai pada taraf deskripsi, yaitu menganalisis dan menyajikan fakta secara sistematik sehingga dapat lebih mudah untuk dipahami dan disimpulkan. Berdasarkan hasil penelitian bahwa jumlah siswa sedikit tidak selalu menunjukan kognitif sosial peserta didik baik, tetapi sebaliknya yaitu kognitif sosial peserta didik di MI Ma'arif Ngampeldento rendah. Hal ini ada beberapa factor yaitu (1) Kurangnya pertukaran ide antar siswa karena sedikitnya jumlah teman di lingkungan sekolah. (2) Minimnya interaksi antar siswa di lingkungan sekolah. (3) tidak terdapat teman sebaya dalam satu sekolah yang bertempat tinggal sama/dekat. (4) letak geografis lingkungan sekolah anak yang berada jauh dari pusat kota. (5) Kurangnya kepedulian orangtua dalam perkembangan kognitif anak. (6) Guru yang kurang cakap dalam menjalankan tugasnya.